PENGARUH INFLASI, BI RATE, DAN NILAI TUKAR RUPIAH TERHADAP DANA PIHAK KETIGA (DPK) PADA PERBANKAN SYARIAH INDONESIA TAHUN 2012-2017 - Nofinawati Nofinawati (IAIN Batusangkar, 2018)
Third Party Funds (TPF) consist of giro, savings and deposits account. The enhancement of TPF is influenced by several factors including Inflation, BI Rate and Rupiah Exchange Rate. In 2013, there was an escalation in Inflation and the BI Rate which was not accompanied by a decrease ofTPF. This is not corresponding with the theory proposed by AuliaPohan. It is said is that if inflation increases then TPF decreases. It is also not fit with Adiwarman Karim's theory of the BI Rate, that is, if there is a profit sharing of sharia funding less than the interest rate, the customer can move to a conventional bank. Whereas in 2013-2015 the Rupiah Exchange Ratedepreciated, whileTPF continued to increase. This condition is also compatible with the theory given by AuliaPohan. The existence of public expectations about the weakening of Rupiah could reduce can be collected by banks.